Hip hop in Cuenca - Cultural Expressions, elements and identities - Diego Illescas Reinoso,; Maribel Acosta Damas, (Technium Social Sciences Journal, 2020)
This ethnographic research will allow us to enter the Hip Hop movement in Cuenca from a social perspective. Its characteristics, identities, artistic and cultural expressions will be known through its elements. Their needs will be made visible as part of the urban cultures of Cuenca, in order to understand how they influence society, whether or not they are excluded, whether or not they enjoy privileges as subjects of law. In this qualitative study, the ethnography technique is applied, whose main objective is to learn about the history of hip hop in the city, its beginnings, the pioneers of the genre; For this we will contextualize this group in the world and we will know the elements that compose it such as: Graffiti, Rap, Break Dance and Turntablism, also called DJing. This study also tries to examine the communication processes and the participation of the hip hop movement in the public space in which decisions are made on matters of interest and how the forms of participation in the construction of public policies are distinguished. Terms such as urban cultures, youth cultures, counterculture and public space are defined to classify hip hop within them, showing how the identity of young people in this genre is constructed.